BEYOND THE CROWN: THE ROLE OF MISS GRAND INTERNATIONAL IN DRIVING SOCIAL AND CULTURAL EVOLUTION - Dony Hermawan (International Journal of Social Science, 2024)
The research aims to understand the perceptions of Miss Grand International contestants as agents of change, as well as to explore the means by which they convey the contest's slogan in the context of peace and cultural missions. This qualitative study employed data collection methods such as interviews and literature reviews, and the data were analyzed through thematic analysis. The study discovered that contestants leverage their platform not only to showcase aesthetics but also as an instrument to foster peace and propagate cultural understanding. The study recommends further empowerment of contestants as agents of change, engaging with local and international institutions, and directing contest promotions towards social and cultural engagement. These findings have implications in the fields of education and cultural diplomacy, highlighting the pivotal role of beauty contests in facilitating social and cultural change, as well as promoting peace and intercultural understanding